Sublingual Tacrolimus: A Pharmacokinetic Evaluation Pilot Study. Issue 1 (10th January 2013) - Tsapepas, Demetra; Saal, Stuart; Benkert, Steven; Levine, Daniel; Delfin, Merdie; Cremers, Serge; Amann, Shawn; Dadhania, Darshana; Kapur, Sandip; Aull, Meredith
<x xml:space="preserve">Abstract</x> Study Objective To evaluate and compare the pharmacokinetic parameters of sublingual and oral tacrolimus in the presence and absence of a drug that interacts with tacrolimus at the intestinal level. Design Prospective, randomized, open‐label, parallel‐group pilot study. Setting Large, urban, academic medical center. Patients Six adults with end‐stage renal disease who were awaiting kidney transplantation; five completed the study. Intervention Patients were randomized in a 1:1 ratio to receive tacrolimus plus a clotrimazole troche (a drug that interacts with tacrolimus at the intestinal level) or tacrolimus plus nystatin suspension. For the tacrolimus route of administration, patients first received sublingual tacrolimus for five doses; after a 2‐day washout period, they received oral tacrolimus for five doses. Measurements and Main Results Demographic characteristics, concomitant medications, tacrolimus dosing information, and steady‐state venous whole blood specimen values after tacrolimus administration were collected. Noncompartmental pharmacokinetics were calculated from the tacrolimus blood concentrations in samples collected at multiple time points after drug administration. The area under the concentration‐time curve from 0–6 hours for sublingual and oral tacrolimus ranged from 27.2–66 and 32.4–76 mg·hour/L, respectively, in the tacrolimus plus clotrimazole group and from 9.3–63 and 4.9–23.2 mg·hour/L, respectively, in the tacrolimus plus nystatin group. The average maximum concentration was higher during sublingual administration than during oral administration: 16.7 versus 12.9 ng/ml in the tacrolimus plus clotrimazole group and 9.5 versus 6 ng/ml in the tacrolimus plus nystatin group. Conclusion An oral‐to‐sublingual tacrolimus dose conversion should be evaluated on an individual basis. A 1:1 dose conversion may be appropriate in the presence of clotrimazole, whereas a 2:1 oral‐to‐sublingual conversion may be appropriate when there are no concomitantly interacting drugs. These findings should be investigated further in pharmacokinetic studies conducted in solid organ transplant recipients.